1639 Va. Acts 224, Act 17 - (:unkn) unknown (My University, 1639)
An act in 1637, which makes it a felony to barter with the Indians repealed, and enacted that for trading with them for arms and ammunition shall be felony, and for other commodities imprisonment at discretion of the Governor and Council.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES